2018 International Joint Conference on Neural Networks (IJCNN) 2018
DOI: 10.1109/ijcnn.2018.8489493
|View full text |Cite
|
Sign up to set email alerts
|

Early Seizure Detection with an Energy-Efficient Convolutional Neural Network on an Implantable Microcontroller

Abstract: Implantable, closed-loop devices for automated early detection and stimulation of epileptic seizures are promising treatment options for patients with severe epilepsy that cannot be treated with traditional means. Most approaches for early seizure detection in the literature are, however, not optimized for implementation on ultra-low power microcontrollers required for long-term implantation. In this paper we present a convolutional neural network for the early detection of seizures from intracranial EEG signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…[3][4][5][6][7] To this end, most studies have utilized either electrocorticography (ECoG) or scalp electroencephalography (EEG) as well as, to a lesser extent, electrocardiography (ECG), and have demonstrated that robust differentiation between preictal and interictal periods as well as early seizure detection is possible with a better-than-chance performance. [8][9][10][11][12][13] Furthermore, seizure forecasting has traditionally performed best when algorithms were trained or optimized at the individual patient level, which often required some sort of training or adjustment phase 8,14 prior to deployment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] To this end, most studies have utilized either electrocorticography (ECoG) or scalp electroencephalography (EEG) as well as, to a lesser extent, electrocardiography (ECG), and have demonstrated that robust differentiation between preictal and interictal periods as well as early seizure detection is possible with a better-than-chance performance. [8][9][10][11][12][13] Furthermore, seizure forecasting has traditionally performed best when algorithms were trained or optimized at the individual patient level, which often required some sort of training or adjustment phase 8,14 prior to deployment.…”
Section: Introductionmentioning
confidence: 99%
“…It also uses spectrogram short-term im-ages and achieved 100% accuracy. Other studies that used spectrograms include [153,158] and [176]. A 3D kernel of Wei et al [169] combined 2D images of an individual-channel EEG time series to obtain a 3D image.…”
Section: Deep Learning Techniquesmentioning
confidence: 99%
“…Currently, most CNN algorithms are higher complexity and executed using CPU or GPUs. A network architecture called SeizureNet on a low-power processing microcontroller unit to predict seizure ( Hügle et al, 2018 ). There is another low-power CNN processor (TrueNorth developed by IBM) has been used for seizure detection ( Merolla et al, 2014 ).…”
Section: Dbs System Oerviewmentioning
confidence: 99%